A pilot randomized clinical trial testing integrated 12‐Step facilitation (iTSF) treatment for adolescent substance use disorder. (1st August 2017) - Kelly, John F.; Kaminer, Yifrah; Kahler, Christopher W.; Hoeppner, Bettina; Yeterian, Julie; Cristello, Julie V.; Timko, Christine
Abstract: Background and Aims: The integration of 12‐Step philosophy and practices is common in adolescent substance use disorder (SUD) treatment programs, particularly in North America. However, although numerous experimental studies have tested 12‐Step facilitation (TSF) treatments among adults, no studies have tested TSF‐specific treatments for adolescents. We tested the efficacy of a novel integrated TSF. Design: Explanatory, parallel‐group, randomized clinical trial comparing 10 sessions of either motivational enhancement therapy/cognitive–behavioral therapy (MET/CBT; n  = 30) or a novel integrated TSF (iTSF; n  = 29), with follow‐up assessments at 3, 6 and 9 months following treatment entry. Setting: Out‐patient addiction clinic in the United States. Participants: Adolescents [ n  = 59; mean age = 16.8 (1.7) years; range = 14–21; 27% female; 78% white]. Intervention and comparator: The iTSF integrated 12‐Step with motivational and cognitive–behavioral strategies, and was compared with state‐of‐the‐art MET/CBT for SUD. Measurements: Primary outcome: percentage days abstinent (PDA); secondary outcomes: 12‐Step attendance, substance‐related consequences, longest period of abstinence, proportion abstinent/mostly abstinent, psychiatric symptoms. Findings: Primary outcome: PDA was not significantly different across treatments [b = 0.08, 95% confidence interval (CI) = –0.08 to 0.24, P  = 0.33; Bayes' factor = 0.28). Secondary outcomes: during treatment, iTSF patients had substantially greater 12‐Step attendance, but this advantage declined thereafter (b = −0.87; 95% CI = –1.67 to 0.07, P  = 0.03). iTSF did show a significant advantage at all follow‐up points for substance‐related consequences (b = −0.42; 95% CI = –0.80 to −0.04, P  < 0.05; effect size range d = 0.26–0.71). Other secondary outcomes did not differ significantly between treatments, but effect sizes tended to favor iTSF. Throughout the entire sample, greater 12‐Step meeting attendance was associated significantly with longer abstinence during ( r  = 0.39, P  = 0.008), and early following ( r  = 0.30, P  = 0.049), treatment. Conclusion: Compared with motivational enhancement therapy/cognitive–behavioral therapy (MET/CBT), in terms of abstinence, a novel integrated 12‐Step facilitation treatment for adolescent substance use disorder (iTSF) showed no greater benefits, but showed benefits in terms of 12‐Step attendance and consequences. Given widespread use of combinations of 12‐Step, MET and CBT in adolescent community out‐patient settings in North America, iTSF may provide an integrated evidence‐based option that is compatible with existing practices.